POLA ARSITEKTURAL PERMUKIMAN DI TEPI AIR KOTA BALIKPAPAN - Suheriah Mulia Devi; Atik Adinda; Agus Fitrianto (Jurnal Arsitektur Display, 2022)
Waterfront areas have different architectural patterns of settlements in each city, so the resulting architectural patterns are also different depending on community activities and adaptation of settlements. This study aims to determine the architectural pattern of the waterfront settlements of Balikpapan City which were selected in the areas in Kelurahan Baru Ulu, Kelurahan Baru Tengah and Kelurahan Margasari on the waterfront. Descriptive analysis method uses data from observations and digitized satellite maps in the area studied, followed by a comparison of the theories of architectural patterns. This study found that in Kelurahan Baru Ulu, Kelurahan Baru Tengah and Kelurahan Margasari on the waterfront, the architectural patterns of settlements in Kelurahan Baru Ulu, Kelurahan Baru Tengah and Kelurahan Margasari on the waterfront were on the architectural pattern of land use forming a linear pattern, then on the architectural pattern The access road has an architectural pattern of angular or grid roads and the architectural pattern of the building mass has a constellation elongated pattern.